PARE0006 Patient empowerment, learning, relaxing, fun, public awareness: a project in the austrian alps. (23rd January 2014) - Wegscheider, P.; Schaffer, G.
Abstract : Background: Patient support groups provide information about rheumatic diseases in order to improve the quality of lives through education and self-management programs, help to get in contact to professional health care and support sharing experiences. Another aim is to raise awareness of the needs of people with arthritis/rheumatism. The Austrian Rheumatism League allocates these and arranges meetings for patients with inflammatory and non-inflammatory rheumatic diseases. Objectives: In summer 2012 a four day meeting in Maria Alm, Salzburg, Austria was organized for patients and health care professionals in order to inform patients about their diseases. Methods: The Austrian Rheumatism League organized a meeting for patients and health care professionals (including physicians, occupational therapists, physical therapists, Qigong-teachers) for four days in the Salzburger Alps. Presentations covering topics like "Is it really arthritis", "Rheumatism in the elderly", "Non-medicamentous pain therapy", "Patient-doctors-relationship", "Infrared therapy" and "Back pain" were held. Interactive workshops on Qigong, drumming and sounds, climbing for patients with rheumatism, gymnastic exercises, cookery courses for arthritis patients, joint protection were performed. A guided herb walk followed by the preparation of herbs for eating and cosmetics was organised as well. Results: Participants emphasized the informal and social aspects of the meeting as an important factor for self-management of their disease. The combination of learning, relaxing and movement were beneficial for a positive result of the lectures. Furthermore the possibility to exchange personal experience was important. All participants, who filled in the questionnaire, graded the project with "very good". Gymnastic exercises and exercises for recreation were graded with "very good" from 69% of the people. 62% of all patients learned a lot of new facts about rheumatism through oral presentations. The lecture about coping strategies was graded with "very good" of 32% and with "good" of 54%. 85% of the participants were diagnosed with arthritis (rheumatoid arthritis, psoriatic arthritis, juvenile idiopathic arthritis), 69% were diagnosed with osteoarthritis, and some of them were diagnosed with both. Conclusions: Following the positive feedback the Austrian Rheumatism League intends to organize special meetings every year to get new participants, to get public awareness and to present recentpatients coping strategies. Disclosure of Interest: None Declared